Karrikins promote germination of physiologically dormant seeds of Chrysanthemoides monilifera ssp. monilifera (boneseed) - Reynolds, C.J.; Long, R.L.; Flematti, G.R.; Cherry, H.; Turner, Shane (2014)
Summary: Physiological dormancy in weed species has significant implications for weed management, as viable seeds may persist in soil seedbanks for many years. The major stimulatory compound in smoke, karrikinolide (KAR1), promotes germination in a range of physiologically dormant weed species allowing targeted eradication methods to be employed. Control of Chrysanthemoides monilifera ssp. monilifera (boneseed), a Weed of National Significance in Australia, may benefit from adopting such an approach. In this study, we hypothesised that seeds of C. monilifera ssp. monilifera exhibit physiological dormancy, germinate more rapidly as dormancy is alleviated, show fluctuations in sensitivity to KAR1 and form a persistent soil seedbank. Seeds responded to 1 μM KAR1 (40-60% germination) even during months (i.e. March, April, July, August) when seeds were observed to be more deeply dormant (control germination: 7-20%). Seeds germinated readily over a range of cooler temperatures (i.e. 10, 15, 20, 20/10 and 25/15°C) and were responsive to KAR2 (~50% germination) as well. Eradication efforts for C. monilifera ssp. monilifera may benefit from use of karrikins to achieve synchronised germination from soil seedbanks, even at times of the year when C. monilifera ssp. monilifera seeds would be less likely to germinate, allowing more rapid depletion of the soil seedbank and targeted control of young plants. © 2013 European Weed Research Society.